SOLVING INVERSE PARTIAL DIFFERENTIAL EQUATIONS PROBLEMS BY USING TEACHING LEARNING BASED OPTIMIZATION ALGORITHM - Boroujeni, A.A; Pourgholi, R; Tabasi, S.H (TWMS journal of applied and engineering mathematics, 2024)
In this paper, a numerical approach is combined with teaching learning based optimization algorithm (TLBO) to solve problems of inverse partial differential equations. The most important point in the way we have presented for these problems, for example an inverse heat condition problem (IHCP), is that we can get an answer to them without any conjecture about the unknown. Numerical experiments in implementation of this method, even without guessing the type of unknown function of the problem, show that these problems can be solved with great accuracy. Accurate results also show that after solving the problems, an excellent estimation of some unknowns can be obtained. Keywords: Inverse partial differential equations problems, TLBO Algorithm, Optimization, Fully implicit method. AMS Subject Classification: 83-02, 99A00.